Center of Twisted Graded Hecke Algebras for Homocyclic Groups - Gan, W.L.; Highfield, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We determine explicitly the center of the twisted graded Hecke algebras associated to homocyclic groups. Our results are a generalization of formulas by M. Douglas and B. Fiol in [J. High Energy Phys. 2005 (2005), no. 9, 053, 22 pages].